Brain Studded with Innumerable Larger Stones: Starry Sky at Night Appearance: Multiple Calcified Giant Tuberculoma with 15 Years of Follow-up - Satyarthee, Guru Dutta; Chandra, P. S.; Mahapatra, A. K. (Indian Journal of Neurosurgery, 2017)
Tuberculosis is rapidly reemerging as a major health problem due to rising incidence of HIV cases across the globe. Central nervous system involvement is rare, but rarely multiple intracerebral granulomas can occur or occasional solitary tuberculoma also develops. The authors report a unique case of 24-year-old woman suffering from pulmonary tuberculosis developed headache and vomiting. Cranial CT scan revealed multiple widespread deposit of intracranial granuloma of sizeable lesion mimicking starry sky at night appearance. Excision of one tuberculoma was done for confirmation of definitive diagnosis, and histopathology was suggestive of tuberculoma. The patient also underwent VP shunt surgery. At last follow-up at 15 years following surgery, she was doing well.
Keywords: multiple intracranial tuberculoma; stones; starry night appearances; hydrocephalus; histopathological diagnosis